Identification of selected genetic polymorphisms in polycystic ovary syndrome in Sri Lankan women using low cost genotyping techniques - Branavan, Umayal; Muneeswaran, Kajan; Wijesundera, Sulochana; Jayakody, Surangi; Chandrasekharan, Vishvanath; Wijeyaratne, Chandrika (PloS one, 2018)
Polycystic ovary syndrome (PCOS), the commonest endocrine disorder affecting young women, appears to be a multigenic trait with contributing genes being unclear. Hence, analysis of polymorphisms in multiple candidate genes is required. Currently available genotyping methods are expensive, time-consuming with limited analytical sensitivity. (i) Develop and validate high resolution melting (HRM) assay and allele-specific real-time quantitative PCR (AS-qPCR) for genotyping selected SNPs associated with PCOS. (ii) Identify selected SNPs and their association with a Sri Lankan cohort of well-characterized PCOS. DNA was extracted from women with well-characterized PCOS from adolescence (n = 55) and ethnically matched controls (n = 110). FTO (Fat mass and obesity associated gene; rs9939609), FSHB (Follicle stimulating hormone beta subunit; rs6169), FSHR (Follicle stimulating hormone receptor; rs6165/rs6166), and INSR (Insulin receptor; rs1799817) genes were genotyped using HRM assay. GnRH1 (Gonadotropin releasing hormone; rs6185), LHB (Luteinizing hormone beta subunit; rs1800447/rs34349826) and LHCGR (Luteinizing hormone/choriogonadotropin receptor; rs2293275) genes were genotyped using AS-qPCR method. Genotyping results were validated using Sanger sequencing. A significant association was observed within FTO gene polymorphism (rs9939609) and PCOS. Genotype frequency of FTO gene (rs9939609)-cases versus controls were TT-36.4% vs.65.4% (p<0.05), AT-23.6% vs.20.9%, AA-40% vs.13.6% (p<0.05). Genotype frequencies of the SNPs GnRH1 (rs6185), FSHB (rs6169), FSHR (rs6165 & rs6166), LHB (rs1800447 & rs34349826), LHCGR (rs2293275) and INSR (rs1799817) were not significantly different between cases and controls (p>0.05). Only the mutant alleles were observed for LHB rs1800447 and rs34349826 SNPs in both groups. The HRM and AS-qPCR assay results had 100% concordance with sequencing results. FTO gene rs9939609 polymorphism is significantly more prevalent among Sri Lankan PCOS subjects while the other selected SNPs of HPG axis genes and INSR gene showed no association. HRM and AS-qPCR assays provide a reliable, fast and user-friendly genotyping method facilitating wider implication in clinical practice.